2020
DOI: 10.1002/aocs.12443
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Foliar Applications of Zinc in the Forms of Free Mineral or Amino Acid Complexed on Qualitative Characteristics of Olive Oil

Abstract: An orchard experiment was conducted during two successive years to evaluate the effectiveness of the foliar application of zinc (Zn) in mineral form (ZnSO4) or chelated with various amino acids (AAC) on the oil content, qualitative indices, and fatty acid profile of olive oil. All Zn sources were applied at a rate of 0.2% during two growth stages; at full bloom (FB) and 15 days after FB. The results showed that Zn, regardless of applied sources, accumulated more Zn in leaves and fruits compared to the control.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The high levels of GA released by seeds in plentiful fruiting years may be responsible for reduced flower development during the next year, and thus be the source of alternate bearing, which is common in olive by lack of lower bud induction. Other researchers have shown that amino acids, notably glutamine and asparagine, are quite beneficial in boosting floral induction in olive and other species (Bastam et al, 2021).…”
Section: Foliar Application Of Bio Stimulants and Amino Acidsmentioning
confidence: 99%
“…The high levels of GA released by seeds in plentiful fruiting years may be responsible for reduced flower development during the next year, and thus be the source of alternate bearing, which is common in olive by lack of lower bud induction. Other researchers have shown that amino acids, notably glutamine and asparagine, are quite beneficial in boosting floral induction in olive and other species (Bastam et al, 2021).…”
Section: Foliar Application Of Bio Stimulants and Amino Acidsmentioning
confidence: 99%
“…Increases in VOO oil content and phenolic compounds were observed when cv. Beledy olive trees were treated with Zn in the form of amino acid chelate (Bastam et al, 2020). In the Chemlali cultivar, the foliar spraying of amino acids, beet molasses and fish by-products as sources of N, P and K resulted in a decrease in the phenol content, contrary to an application of a formulation based on calcium (Ca), which led to a significant increase in phenolic compound contents (Dabbaghi et al, 2019).…”
Section: Other Nutrients That Influence Voo Phenolsmentioning
confidence: 99%